2021
DOI: 10.5194/acp-2021-700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circum-Antarctic abundance and properties of CCN and INP

Abstract: Abstract. Aerosol particles acting as cloud condensation nuclei (CCN) or ice nucleating particles (INP) play a major role in the formation and glaciation of clouds. Thereby they exert a strong impact on the radiation budget of the Earth. Data on abundance and properties of both types of particles are sparse, especially for remote areas of the world, such as the Southern Ocean (SO). In this work, we present unique results from ship-borne aerosol-particle-related in situ measurements and filter sampling in the S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 75 publications
(103 reference statements)
5
14
0
Order By: Relevance
“…This, together with our observations, implies that air masses, at least those at lower altitudes, will quickly be enriched in INPs when coming into contact with continental or more generally terrestrial sources. A similar observation was also made by Tatzelt et al (2021) based on observations performed in the frame of a circumvention of Antarctica.…”
Section: Contribution Of Biogenic Inpssupporting
confidence: 79%
See 1 more Smart Citation
“…This, together with our observations, implies that air masses, at least those at lower altitudes, will quickly be enriched in INPs when coming into contact with continental or more generally terrestrial sources. A similar observation was also made by Tatzelt et al (2021) based on observations performed in the frame of a circumvention of Antarctica.…”
Section: Contribution Of Biogenic Inpssupporting
confidence: 79%
“…Welti et al (2020) reported on a collection of ship-based INP measurements and found that maritime N INP in the South Temperate Zone (23.5-66.5 • S) was lower than that in the North Temperate Zone (23.5-66.5 • N). In general, maritime N INP were lower than continentally influenced N INP , indicating that land is a stronger source of INP than the ocean (Welti et al, 2020;Tatzelt et al, 2021). López et al (2018) collected soil dust in northern Patagonia and confirmed its ability to be ice active, which points out that natural mineral dust particles may be an important source of INPs in the Southern Hemisphere.…”
Section: Introductionmentioning
confidence: 90%
“…This, together with our observations, implies that air masses, at least those at lower altitudes, will quickly be enriched in INP when getting into contact with continental or more generally terrestrial sources. A similar observation was also made by Tatzelt et al (2021) based on observations performed in the frame of a circumvention of Antarctica.…”
Section: Contribution Of Biogenic Inpssupporting
confidence: 79%
“…Gong et al (2020) examined INPs from the ocean, the ambient environment and from cloud water at the Cape Verde islands, and found that marine aerosols from sea spray production only explained a very minor fraction of N INP in the atmosphere and in cloud water. Tatzelt et al (2021), having collected data in the Southern Ocean and Welti et al (2020), examining a broader, more global data-set found that the ship-based measurements of ambient N INP show 1 to 2 orders of magnitude lower mean concentrations for clean marine conditions than for continental observations. Therefore, INP in our study most likely originated from land and more evidence for this is discussed in the following sections.…”
Section: Results From Previous Studies On Inp Added Tomentioning
confidence: 99%
See 1 more Smart Citation